Ukama Ustawi: Establishing a Community of Spirit - Synthesis of Perspectives - Reos Partners (International Water Management Institute, 2022)
This Synthesis of Perspectives is a key part of co-designing the Community of Spirit (COS) for Ukama Ustawi (UU). This process included a series of interviews, a survey distributed to the entire UU community, and a Mentimeter at the Core Partners meeting on the 9 Sep. This process is helping to surface how this COS can best serve the UU community as well as how the UU team (staff and partners) want to work together (both the agreements around the quality and principles for engagement, as well as the practical aspects such as cadence and types of meetings (e.g. in-person, virtual, etc).